ANALISIS PENGARUH KOMPETISI, SIZE, CAPITALIZATION DAN LOANS INTENSITY TERHADAP EFISIENSI BANK (Studi Kasus Bank Umum Konvensional di Indonesia Periode tahun 2008-2012) - Farida A., Nabila H.N.; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
Deregulation in banking industry, which is started with API policy and its derivatives in 2004, makes the industry change a lot, whether in its structure or interaction. This will affect banks performance in Indonesia banking industry. One of the most noted indicator is bank efficiency.Â This study is analyzing the effect of competition, size, capitalization and loans intensity to conventional bank efficiency in 2008 to 2012 period. Banking efficiency will be measured with stochastic frontier approach (SFA) and banking competition will be measured with Lerner Index. Analysis of the the effect of competition, size, capitalization and loans intensity to conventional bank efficiency will be conducted using ordinary least square (OLS) data panel method.The result of this study shows that competition level that occurred in conventional banks gives negative effect to bank efficiency, while bank size gives positive effect to bank efficiency. Capitalization gives negative effect, but insignificant, while loans intensity, though insignificant,Â gives positive effect to the efficiency.